THE INFLUENCE OF ECOENZYME ON METHANE (CH4) LEVELS IN LANDFILL WASTE - Nuri Trihasti Miranda; Fuad Jaya Miharja; Sukarsono (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2023)
The effect of Ecoenzyme and waste thickness on methane gas levels contained in waste. Utilization of Ecoenzyme in reducing pollutant power in the environment. Obstacles in waste processing and the consequences of excess landfill can damage the earth's layer, becoming a global warming event. The objective of this study was to determine how much influence the concentration of ecoenzyme in reducing methane gas pollutants in waste. The sequence of research conducted was: 1) Looking for and determining the location at the Supit Urang Landfill in Malang City; 2) Make ecoenzyme in the mature period (+ 3months); 3) Make plotting according to the treatment; 4) Measuring methane gas content before and after treatment; 5) Record results. After conducting research activities at the Supit Urang landfill in Malang City, there was a decrease in methane gas in the treatment of ecoenzyme concentrations of 6%, 8%, and 10% at a thickness of 10cm and 30 cm, this shows that there is an influence of concentration and thickness on the reduction of methane gas.